The Development of Faith, Piety, and Noble Morals in Civics Education - Achmad Panji Waluyo; Suwarma Al Muchtar (Department of Civic Education, 2020)
This research was conducted to describe approaches, strategies, obstacles, efforts to develop the faith, piety, and noble morals towards students character in SMP Negeri 10 Bandung. The approach chosen is a qualitative approach with the method is case study. Data collection techniques using interview techniques, observation techniques, and study documentation. Techniques in data analysis namely collection data, reducing data, presenting data, and drawing conclusions. The final results of this study show that there are various approaches and strategies used by the informants. Then there are also obstacles faced, both from students, the social environment, and government policies. Then there are efforts made together, both of schools, communities, and parents of students. So that the approach and strategy gives good results in developing the faith, piety, and noble morals towards the character of students.